(untitled) (Praxis Educativa, 2024)
The educational policies of the last decades in Argentina have profoundly modified the system, the population and the expectations and demands towards education. In this framework, the choice of secondary school appears as an extremely important aspect in the processes of socio-educational inequality. This article is based on two qualitative research projects on school choice and family strategies in lower and upper class contexts respectively in the city of Córdoba. The results allow us to refute some assumptions of the academic tradition, such as the assumption that lower class families do not choose or that upper class families have all the options. We identify that choice is differentially signified according to social class and involves strategies of sounding, prioritizing and choosing in order to shorten the distance between what is possible and what is desired.